En amerikansk Grundtvig-oversættelse. Selected Writings of N. F. S. Grundtvig, edited by Johannes Knudsen - Nielsen, Niels Lyhne (Grundtvig-studier, 1977)
An American Translation of Grundtvig Selected Writings of N. F. S. Grundtvig - edited and with an introduction by Johannes Knudsen. Philadelphia 1976. Fortress Press USD 5.95. Reviewed by Niels Lyhne Jensen.This is the first anthology of Grundtvig’s writings in English and must be regarded as an event in the field of Grundtvig literature. Translating Grundtvig is a formidable task. His choice of words, his syntax, his imagery and world of ideas present such difficulties to the translator that by comparison translating Kierkegaard or Hegel must seem like child’s play. Furthermore, a presentation of Grundtvig’s works that includes his prose but not samples of his poetry would give a distorted picture. Professor Johannes Knudsen and his two collaborators, Dr. Enok Mortensen and Dr. Ernest D. Nielsen have approached the task with first-rate qualifications. There are no misunderstandings in the translations as regards language and contents, and both the anthology as a whole and the individual sections contain well-informed introductions, although they are sadly deficient in information about Grundtvig’s works. But the translators’ familiarity with the material has ensured a selection that in general is substantial and many-sided.The first and largest section includes among other things selections from Kirkens Gjenmæle (The Response of the Church), the introduction to Nordens Mytologi (Nordic Mythology) 1832, and passages from Den Christelige Børnelærdom (Christian Childhood Teachings). The inclusion of these would suggest a desire to meet the demands of American readers interested in Grundtvig’s attitude to Kierkegaard’s attack on the Church in 1855. This also seems to have influenced the choice of sermons - none before 1839, but as many as three from 1855. It is hardly defensible to ignore Søndagsbogen (The Sunday Book) completely.The poetry section consists mainly of hymns and poems on education methods, mostly from after 1832. Included among the hymns of the Holy Spirit are translations of two not very outstanding examples - one of them back to English! Surely there were plenty of others to choose from.The final section contains examples of Grundtvig’s educational writings and his polemics. It includes amongst others Skolen for Livet {The School for Life) and the proposal for a Northern university from 1837. The choice could hardly be bettered; it is substantial, varied and entertaining.The absence of selections from Grundtvig’s mythological and historical works is regrettable; so too is the lack of autobiographical texts. Grundtvig’s interpretation of myth might win interest outside the circle of Grundtvig students. The passages chosen are reproduced in an abridged and contracted form. This approach raises a number of problems. Even though a row of dots is used to denote an abridgement, the anthology leaves in the lurch the reader who wants to read the original Danish with the translation as a ‘crib*. Such a method is not unlikely; but no information is given as to which edition has been used for the translations, nor which pages of this edition are included.The translation does not attempt to give a convincing representation of Grundtvig’s style. The chief editor has drawn attention to the difficulty of finding English equivalents of Grundtvig’s major concepts, such as ’folkelighed’ (the feeling and quality of belonging to a nation) and ’anskuelse’ (a particular way of looking at a problem). Just as English has retained Kierkegaard’s ’angst’, so does Johannes Knudsen wish to retain Grundtvig’s ’anskuelse’. Thismay be acceptable with one particular word but in general it is not a good practice to fellow.The texts of the hymns included here leave one with the feeling that a number of them have been taken from available Danish-American song-books. But there is no mention of the publishing company or the translator. These translations are for devotional use - aesthetic and philological considerations take second place - a legitimate practice which Grundtvig himself employed.Among the freely paraphrased translations Johannes Knudsen’s rendering of 'Udrundne er de gamle Dage’ (Relentlessly the human story) is given pride of place by the reviewer. But there is also an example of Grundtvig’s pithy text being translated by colourless Christian banalities in *Vidunderligst af alt på Jord (Most wondrous is of all on earth). Amongst the most successful pieces are *Blomstre som en Rosengaard’ (Blossom shall the wilderness) by Johannes Knudsen, and 7 al sin Glans nu straaler Solen (The Sun now Shines in all its Splendour) by Søren D. Rodholm.In his introduction Johannes Knudsen discusses the problem of translating Grundtvig. He does not think that prose translations of the poems are a good idea, though he himself renders one poem in this way - *Menneske først og kristen saa (Man first and then Christian). This reviewer is of the opinion that this is the only practicable approach; for it enables the reader to get closer to Grundtvig’s special imagery.A more extensive and thorough-going translation of Grundtvig will be able to take advantage of its faults and merits. But this book is in itself in many ways a noteworthy achievement.